Which Road to Recovery?: Factors Influencing Postacute Stroke Discharge Destinations: A Delphi Study. Issue 3 (28th October 2021) - Stein, Joel; Rodstein, Barry M.; Levine, Steven R.; Cheung, Ken; Sicklick, Alyse; Silver, Brian; Hedeman, Robin; Egan, Abigail; Borg-Jensen, Pamela; Magdon-Ismail, Zainab; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The criteria for determining the level of postacute care for patients with stroke are variable and inconsistent. The purpose of this study was to identify key factors influencing the selection of postacute level of care for these patients. Methods: We used a collaborative 4-round Delphi process to achieve a refined list of factors influencing postacute level of care selection. Our Delphi panel of experts consisted of 32 panelists including physicians, physical therapists, occupational therapists, speech-language pathologists, nurses, stroke survivors, administrators, policy experts, and individuals associated with third-party insurance companies. Results: In round 1, 207 factors were proposed, with subsequent discussion resulting in consolidation into 15 factors for consideration. In round 2, 15 factors were ranked with consensus on 10 factors; in round 3, 10 factors were ranked with consensus on 9 factors. In round 4, the final round, 9 factors were rated with Likert scores ranging from 5 (most important) to 1(not important). The percentage of panelists who provided a rating of 4 or above were as follows: likelihood to benefit from an active rehabilitation program (97%), need for clinicians with specialized rehabilitation skills (94%), need for active and ongoing medical management and monitoring (84%), ability to tolerate an active rehabilitation program (74%), need for caregiver training to return to the community (48%), family/caregiver support (39%), likelihood to return to community/home (39%), ability to return to physical home environment (32%), and premorbid dementia (16%). Conclusions: This study provides an expert, consensus-based set of key factors to be considered when determining where stroke patients are discharged for postacute care. These factors may be useful in developing a decision support tool for use in clinical settings.